2006
DOI: 10.1080/13625180500456742
|View full text |Cite
|
Sign up to set email alerts
|

The predictors of retained products of conception following first-trimester pregnancy termination with manual vacuum aspiration

Abstract: Our study suggests that the frequency of RPC after MVA has been affected by current pregnancy-related factors such as patient age, BMI, and gestational age rather than the prior obstetric history of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…An extensive review of the literature on uterine evacuation for induced early abortion have documented that MVA was highly effective achieving complete uterine evacuation in 98% cases. 22 Present study shows that increased patient age, parity, extremes of gestational age and high BMI are associated with incomplete evacuation which is comparable with result of Inal et al 23 World Health Organization has listed MVA as an effective and safe method of uterine evacuation and hence the technique is being employed extensively in developing world under minimal anesthesia or sedation in managenment of incomplete miscarriages. 25 However, there in minimal available data regarding its use in missed miscarriages.…”
Section: Discussionsupporting
confidence: 90%
“…An extensive review of the literature on uterine evacuation for induced early abortion have documented that MVA was highly effective achieving complete uterine evacuation in 98% cases. 22 Present study shows that increased patient age, parity, extremes of gestational age and high BMI are associated with incomplete evacuation which is comparable with result of Inal et al 23 World Health Organization has listed MVA as an effective and safe method of uterine evacuation and hence the technique is being employed extensively in developing world under minimal anesthesia or sedation in managenment of incomplete miscarriages. 25 However, there in minimal available data regarding its use in missed miscarriages.…”
Section: Discussionsupporting
confidence: 90%
“…It has recently been reported that RPOC after firsttrimester pregnancy termination was more commonly found when the procedure was performed at a more advanced gestational age. 21 Therefore, in our study, an increasing incidence of postabortion myometrial hypervascularity as gestational age advances most probably results from the increasing incidence of RPOC.…”
Section: 13mentioning
confidence: 92%
“…Some authors describe RPOC as non-villous trophoblastic tissue, chorionic villi or foetal membranes, and they state that decidua alone does not fall within the definition [3][4][5]. Others say that RPOC consist of the gestational sac, the decidua capsularis, chorionic villi or the embryo itself [6]. Still others argue that RPOC are from placental origin, and thus, that the presence of chorionic villi in RPOC is necessary [1,7].…”
Section: Introductionmentioning
confidence: 99%